2016
DOI: 10.1002/cncr.30160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insurance status on survival of adults with glioblastoma multiforme: A population‐based study

Abstract: Variations existed in insurance status within the GBM population. Uninsured status and Medicaid insurance suggested shorter survival compared with non-Medicaid insurance among a population of patients with GBM. Cancer 2016;122:3157-65. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
51
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 48 publications
12
51
1
Order By: Relevance
“…In a population-based study by Rong et al, using the SEER database, the authors found that patients with non-Medicaid insurance had a longer median overall survival, whereas those with Medicaid or no insurance did not have this survival benefit. 26 In our study we found similar results to that of Rong et al, with our insured patient cohort having a median overall survival that was almost twice as long when compared to survival of uninsured patients. However, unlike the findings by Rong et al, in our study there was no statistical significance in the median overall survival among the Medicaid, Medicare, and private insurance groups, which could potentially reflect greater equality between these coverages in our regional market compared to the diverse states that comprise the SEER database.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In a population-based study by Rong et al, using the SEER database, the authors found that patients with non-Medicaid insurance had a longer median overall survival, whereas those with Medicaid or no insurance did not have this survival benefit. 26 In our study we found similar results to that of Rong et al, with our insured patient cohort having a median overall survival that was almost twice as long when compared to survival of uninsured patients. However, unlike the findings by Rong et al, in our study there was no statistical significance in the median overall survival among the Medicaid, Medicare, and private insurance groups, which could potentially reflect greater equality between these coverages in our regional market compared to the diverse states that comprise the SEER database.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the literature, our cohort comprised 9.04% uninsured patients, 12.7% with Medicaid, 37.01% with Medicare, and 41.24% with private insurance. 22,26 In this single-institution study, we found insurance status, one of the many indicators of access to health care, to be a major prognostic factor for patients with newly diagnosed GBM, consistent with the findings in a recent study by Rong et al 26 in which a large population cancer registry was used.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations